Functional Trait Responses of Macrobenthos to Anthropogenic Pressure in Three Temperate Intertidal Communities - Dong, Jian-Yu; Zhao, Linlin; Yang, Xiaolong; Sun, Xin; Zhang, Xiumei (Frontiers in Marine Science, 2021)
With the increasing impact of human activities on marine ecosystems, there is a growing need to assess how the components of marine ecosystems (e.g., macrobenthos) respond to these anthropogenic pressures. In this study, the trait-based approach was used to assess the effects of anthropogenic pressures represented by the area of land-based aquaculture pond (PondArea) and heavy metals on the macrobenthic communities in three intertidal zones (AO, RW and XD) of Laoshan Bay, Shandong Peninsula, China. Compared with RW and XD, AO was under more pressure in terms of the average concentrations of heavy metals and TOC in sediments as well as PondArea. Fuzzy correspondence analysis (FCA) showed that there were significant differences in the composition of functional traits among the three regions (PERMANOVA; p < 0.05). In the highly polluted area, macrobenthic communities exhibited a combination of traits such as relatively short life span, weak mobility, feeding on deposits, and more tolerant to organic matter, while in a less polluted area, they exhibited a combination of traits such as relatively long life span, relatively high mobility, and more sensitive to organic matter. The RDA results showed that the distribution of the trait modalities was significantly affected by heavy metals (Hg and Cd), TOC, PondArea and sampled location. Variation partitioning analysis (VPA) indicated that the shared influence of sediment-related pollution factors and PondArea contributed most to the variance of the functional traits, which implied that human activities directly and/or indirectly lead to changes in functional traits of macrobenthic communities in the intertidal zones.